2015
DOI: 10.1007/s11051-015-3003-8
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional Bi2MoO6 nanotubes: controllable synthesis by electrospinning and enhanced simulated sunlight photocatalytic degradation performances

Abstract: One-dimensional Bi 2 MoO 6 nanotubes were successfully synthesized by the electrospinning technique in combination with the calcination process. The as-prepared samples were characterized by thermogravimetric and differential scanning calorimetry, Fourier transform-infrared spectroscope, microscopic Raman spectrometer, X-ray diffraction, scanning electron microscope, and transmission electron microscope. The hollow morphology of the Bi 2 MoO 6 nanotubes can be obtained after calcining the electrospun gel nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…The survey spectrum of BMO–C10 (Figure a) reveals the existence of Bi (∼9%), Mo (∼4.2%), O (∼25.7%), C (∼40%), and N (∼21.1%) elements without any impurities. In Figure b, the observed two strong peaks at binding energies of 158.9 and 164.2 eV corresponding to Bi 4f 7/2 and Bi 4f 5/2 , respectively, indicate the trivalent oxidation state for bismuth (Bi 3+ ) ions in the composite with a typical spin–orbit splitting value of 5.3 eV. ,, Similarly, spin–orbit splitting of Mo corresponding to Mo 3d 5/2 (232.2 eV) and Mo 3d 3/2 (235.4 eV) is observed in the Mo 3d spectrum, as shown in Figure c, which indicates that the Mo ions in BMO–C10 are in the +6 oxidation state with a spin–orbit splitting energy of 3.2 eV. The deconvoluted core level spectrum of oxygen 1s spectrum (Figure d) showed two distinct peaks at 530.1 and 531.6 eV, corresponding to the metal–oxygen and surface-adsorbed OH groups, ,, respectively, which indicated that the oxidation state of oxygen ions in the system is −2. Similarly, Figure e shows the deconvoluted carbon 1s spectrum, where the three peaks at 284.7, 288.5, and 285.9 eV can be assigned to the graphitic or aliphatic C–C/CC, CO, and C–OH/C–O groups, , respectively.…”
Section: Resultsmentioning
confidence: 87%
“…The survey spectrum of BMO–C10 (Figure a) reveals the existence of Bi (∼9%), Mo (∼4.2%), O (∼25.7%), C (∼40%), and N (∼21.1%) elements without any impurities. In Figure b, the observed two strong peaks at binding energies of 158.9 and 164.2 eV corresponding to Bi 4f 7/2 and Bi 4f 5/2 , respectively, indicate the trivalent oxidation state for bismuth (Bi 3+ ) ions in the composite with a typical spin–orbit splitting value of 5.3 eV. ,, Similarly, spin–orbit splitting of Mo corresponding to Mo 3d 5/2 (232.2 eV) and Mo 3d 3/2 (235.4 eV) is observed in the Mo 3d spectrum, as shown in Figure c, which indicates that the Mo ions in BMO–C10 are in the +6 oxidation state with a spin–orbit splitting energy of 3.2 eV. The deconvoluted core level spectrum of oxygen 1s spectrum (Figure d) showed two distinct peaks at 530.1 and 531.6 eV, corresponding to the metal–oxygen and surface-adsorbed OH groups, ,, respectively, which indicated that the oxidation state of oxygen ions in the system is −2. Similarly, Figure e shows the deconvoluted carbon 1s spectrum, where the three peaks at 284.7, 288.5, and 285.9 eV can be assigned to the graphitic or aliphatic C–C/CC, CO, and C–OH/C–O groups, , respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Seeking new catalysts that can make full use of sunlight, especially the visible light portion, is a meaningful topic. Bi 2 MoO 6 , a nontoxic and visible light-responsive semiconductor, is promising for making photocatalysts. Bi 2 MoO 6 photocatalysts with different morphologies or structures (e.g., nanoparticles, nanotubes, nanosheets, flowerlike structures, , and hollow microspheres , ) have been developed. However, the recombination of photogenerated carriers is still a serious problem when using pristine Bi 2 MoO 6 as a photocatalyst .…”
Section: Introductionmentioning
confidence: 99%
“…紫外光; 自身光生电子-空穴对易复合, 又导致光量 子效率较低, 限制了其实际应用 [3][4] 。 铋基光催化材料以其独特的能带结构和较高的 光腐蚀稳定性而引起了广泛关注 [5] 。其中 Bi 2 MoO 6 性能稳定、带隙较窄(2.5~2.8 eV)、形貌可控, 已经 制备出纳米片 [6] 、纳米球 [7] 、纳米纤维 [8] 、纳米墙 [9] 、 纳米花 [10] 和纳米管 [11] 等不同形貌的 Bi 2 MoO 6 光催 化剂, 并证实其光催化性能与材料的形貌和电荷分 离效率密切相关。但纯 Bi 2 MoO 6 光吸收效率低、电 荷转移速率慢和光致电荷载流子复合几率高, 致使 其光催化性能仍不能满足实际应用需求 [12] 。 自 Awazu 等 [13] 首次提出贵金属表面等离子体光 催化, 并成功将金属 Au 纳米粒子应用于开发具有可 见光驱动的光催化材料以来, Au、Ag、Pt 等贵金属光 催化引起人们广泛的研究兴趣 [14][15][16][17] 。但是这些光催化 剂价格昂贵成为大规模推广应用的瓶颈, 而半金属 Bi 具有成本低、带隙小、能带重叠少等优点, 特别是当 Bi 颗粒小于几十纳米时, 能够产生与贵金属相似的表 面等离子体共振(SPR)效应 [18][19] , 成为贵金属表面等 离子体光催化最理想的替代品。近年来, 有关研究者…”
unclassified